2021
DOI: 10.1186/s12877-021-02377-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of frailty with health service utilisation and health care expenditure in sub-Saharan Africa: evidence from Côte d’Ivoire

Abstract: Background Frailty, a syndrome resulting in heightened risk of negative outcomes for older adults, is increasing across the globe. However, little is known about the health service impacts of frailty in low-income countries (LICs), and in particular, sub-Saharan Africa (SSA). This study explores the relationship between frailty and health service 1) utilisation and 2) expenditure within Côte d’Ivoire. Methods Participants aged 50 years and over par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Our study found that the mean FI was 0.23, which is similar to some studies in China ( Stolz et al, 2019 ) and South Africa ( Ambagtsheer & Moussa, 2021 ), but higher than the findings in Brazil ( Silva & Almeida, 2019 ), the UK ( Gale et al, 2018 ), Canada ( Perez-Zepeda et al, 2021 ) and other European countries ( Stolz et al, 2019 ). The different results may be due to the indicators for constructing FI in different studies and different socioeconomic statuses between developing and developed countries.…”
Section: Discussionsupporting
confidence: 88%
“…Our study found that the mean FI was 0.23, which is similar to some studies in China ( Stolz et al, 2019 ) and South Africa ( Ambagtsheer & Moussa, 2021 ), but higher than the findings in Brazil ( Silva & Almeida, 2019 ), the UK ( Gale et al, 2018 ), Canada ( Perez-Zepeda et al, 2021 ) and other European countries ( Stolz et al, 2019 ). The different results may be due to the indicators for constructing FI in different studies and different socioeconomic statuses between developing and developed countries.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies has also suggested that frailty was associated with healthcare expenditure, both in developed and developing countries ( 5 , 8 11 , 15 , 16 ). Several small-sample studies have shown that frailty was associated with increased hospitalized costs for patients with colorectal surgery ( 6 ), cardiac surgery ( 13 ), or transcatheter aortic value implantation ( 35 ).…”
Section: Discussionmentioning
confidence: 86%
“…Frailty describes a decline in physiological capacity across multiple organ systems, characterized by an increased vulnerability to stressors (3). The condition of frailty is associated not only with a myriad of adverse outcomes (4) but also with increased healthcare costs (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, there is no gold standard assessment instrument for frailty (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Though comparisons must be drawn cautiously due to the high proportion of missing data, the prevalence using the FP represents a much greater burden of frailty than in the community in Tanzania, where the phenotypic prevalence in the Hai District was 9.3% [ 15 ]. This is an expected finding, given that older people living with frailty are more likely to utilise hospital services [ 31 ].…”
Section: Discussionmentioning
confidence: 87%